Quantifying Human Preferences for Polyrhythms. - Steinhauer, Grant. (Tufts Archival Research Center, 2018)
This study investigates the pleasantness ratings of polyrhythms formed by expressing the frequency ratios of common pitch intervals into metronomic pulse trains with corresponding tempo ratios. Pleasantness ratings of the polyrhythms are shown to be significantly correlated with the pleasantness ratings of their corresponding pitch counterparts, especially when the polyrhythms are condensed into 2-second cycle durations.